The Combination of Coagulation and Stretchability Temperature on Mozzarella Chemical Quality with Lime Juice as Acidifier - Purwadi Purwadi (Faculty of Animal Science Universitas Brawijaya, 2008)
This research was conducted about Mozzarella cheese manufacturing using lime juice as acidifier. The objectives of current research were to know the potency of lime juice as acidifier to make Mozarella cheese and its chemical quality. The method used in this research was 4x4 factorial design consisted of two factors. The first factor was coagulation temperature (G) namely : G1=30 oC, G2=35 oC, G3=40 oC, and G4=45 oC, and the second factor was stretchable temperature (M) namely: M1=70 oC, M2=75 oC, M3=80 oc, and M4=85 oC. Variables measured were whey protein level, whey dry matter, moisture stretchable protein and moisture stretchable dry matter. Variation analysis showed that the interaction between coagulation temperature and strechable temperature gave no significant difference (P<0.05). The best combination treatment was coagulatiomÂ temperature 30 oC with stretchable temperature 75 oC. Keywords: coagulation, stretchability, chemical quality, mozarella cheese, lime juice